ANALYSIS OF ORGANIC MATTER CONTENT IN SEDIMENTS AND MACROZOOBENTHOS ABUNDANCE IN PAKNING RIVER WATERS, BENGKALIS REGENCY, RIAU PROVINCE - Dwigantara, M. Fadhol; Amin, Bintal; Efriyeldi, Efriyeldi (Asian Journal of Aquatic Sciences, 2023)
This research was conducted in April 2021 to analyze organic matter content in the sediment and the abundance of macrozoobenthos. The purpose of this study was to analyze the content of organic matter in sediments and their relationship with the abundance of macrozoobenthos in the waters of the Pakning River, Bengkalis Regency, Riau Province. Sediment and macrozoobenthos samples were taken from the waters of the Pakning River, Bengkalis District, Riau Province. The method used in this research is a survey method. Sampling was determined using purposive sampling at four different stations. The results of this study indicate that the organic matter content of sediment in the waters of the Pakning River has a percentage of 6.73-12.76%. The highest organic matter content is at station 1 of 12.76% and the lowest organic matter content is at station 4 of 6.73%. The highest average abundance of macrozoobenthos was 19.26 ind/m2 at station 1 with the dominant species being Anadara granosa. Connection between organic sediment and abundance of macrozoobenthos has a linear regression equation y = 1.8442 +0.1662x with a coefficient (R2) of 0.1491 which means that the effect of organic matter in the waters of the Pakning River is 14.9% while 85.1% is influenced by other factors. The value of 0.38 indicates that the relationship between organic matter and the abundance of macrozoobenthos is, a moderate relationship.